Penegakan Kode Etik Kejaksaan terhadap Jaksa Yang Melakukan Tindak Pidana Narkotika - Nurhadisyah Mulqi Putri; Puti Priyana (Wajah Hukum, 2021)
As indicated by Article 30 passage 1 letter b of the Prosecutor's Law, the Public Prosecutor as a public investigator has the power to indict instances of criminal demonstrations. For this situation, particularly opiates wrongdoings as managed in the Law on Narcotics and can't be isolated from the criminal equity framework. The job of the investigator's office in arraigning opiates crooks is to facilitate with other policemen, particularly BNN officials, the Police, and PPNS. This review utilizes a regularizing juridical methodology, by looking at and deciphering hypothetical issue concerning the standards, originations, precepts and legitimate standards identifying with law requirement against investigators who carry out opiates violations. The outcomes show that the Narcotics Law doesn't manage the examiner's office in opiates cases; they just endorse the beginning of the examination and get the minutes of the examination. The most prevailing deterrent is knowing current realities on the ground considering the way that the Public Prosecutor can't explore opiates cases in the field. opiates wrongdoing cases since opiates are identified with the public interest. The law on opiates should give the examiner the position to become agents.